The Effect of Celebrity Endorsement on Purchase Intention of Adidas Products Mediated by Customer’s Attitude Toward Brand - Dewi Wuisan; Ishmael Lamisi Kananda; Muhammad Adha Saputra; Muhammad Rakha Dinata (ADI Publisher, 2020)
This study aims to determine the effect of celebrity endorsment on purchase intention of Adidas which mediates customer attitude towards brand. Big companies currently use celebrity to be able to market their products, one of which is a sportwear company, namely Adidas, which uses Kanye West as a celebrity endorser to be able to market their products. Companies are expected to pay attention to or see celebrity from several variables, namely celebrity trustworthiness, celebrity expertise, celebrity attractiveness, celebrity similarity, celebrity liking, celebrity familiarity and celebrity match-up congruence with the brand / product. This study uses individual primary data collection methods using a questionnaire. Researchers took respondents who live in the Tangerang and Jakarta areas. Respondents in this study were 150 respondents. This study uses data processing using Partial Least Square - Structural Equation Modeling (PLS-SEM) and is processed using SmartPLS software. The results showed that the celebrity endorsement variable had a positive and significant effect on the response from prospective Adidas customers, so that customers would do Purchase Intention mediated by customer attitude toward the brand.